2023
DOI: 10.1182/bloodadvances.2022008403
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab for the treatment of disease relapse after allogeneic hematopoietic stem cell transplantation

Abstract: A failed graft-versus-tumor (GVT) effect is a common mechanism of relapse following allogeneic hematopoietic cell transplantation (alloHCT). While targeting the PD-1/PD-L1 axis may restore GVT effects, PD-1 blockade exacerbates graft-versus-host disease (GVHD) in murine models, and severe GVHD can occur in patients treated with anti-PD-1 therapy after alloHCT. We therefore developed a prospective study to assess the safety and efficacy of pembrolizumab in patients relapsing after alloHCT. Eligible patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Blocking the PD1/PD-L1 interaction in malignancies that acquire PD-L1 as an adaptative response to immune pressure relieves T cell inhibition exerted by tumor cells on CD8+ T cells against minor histocompatibility antigens ( 26 ). Early-phase clinical trials have shown the efficacy and feasibility of PD-1 blockade in the post-allo-HSCT relapse setting ( 27 , 28 ). Our data support the potential of CPIs even after DLI failure and suggest a potential synergistic effect between allo-HSCT and checkpoint blockade therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking the PD1/PD-L1 interaction in malignancies that acquire PD-L1 as an adaptative response to immune pressure relieves T cell inhibition exerted by tumor cells on CD8+ T cells against minor histocompatibility antigens ( 26 ). Early-phase clinical trials have shown the efficacy and feasibility of PD-1 blockade in the post-allo-HSCT relapse setting ( 27 , 28 ). Our data support the potential of CPIs even after DLI failure and suggest a potential synergistic effect between allo-HSCT and checkpoint blockade therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed brentuximab with DLI for HL relapsing after allo-HSCT to be effective with minimal toxicity, hypothesizing the immunomodulating role of BV in preventing GvHD ( 43 , 44 ). A recent study highlights the use of pembrolizumab to induce the GVL effect in relapsed hematologic malignancies after HSCT ( 28 ). The association of both agents has rarely been described in the literature but has mostly been described in r/r HL as a bridge to autologous transplant ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of clinical trials on leukemia treatment with PD-1/PD-L1 mAbs have been performed nowadays. The overall response rate (ORR) of pembrolizumab alone is 0% in eight patients with AML ( 158 ). When combined with cytarabine, the ORR is 46% ( 116 ); the former grade 3–4 iRAEs are 25% ( 158 ), and the latter grade ≥3 iRAEs are 14% and self-limiting ( 116 ).…”
Section: Efficacy Of Pd-1/pd-l1 Mabs Treating Leukemia Alone or In Co...mentioning
confidence: 99%
“…The overall response rate (ORR) of pembrolizumab alone is 0% in eight patients with AML ( 158 ). When combined with cytarabine, the ORR is 46% ( 116 ); the former grade 3–4 iRAEs are 25% ( 158 ), and the latter grade ≥3 iRAEs are 14% and self-limiting ( 116 ). The median recurrence-free survival (RFS) of AML patients treated with nivolumab alone is 8.48 months ( 159 ).…”
Section: Efficacy Of Pd-1/pd-l1 Mabs Treating Leukemia Alone or In Co...mentioning
confidence: 99%
See 1 more Smart Citation